Dynamische Problemlösekompetenz: ein bedeutsamer Prädiktor von Problemlöseleistungen in technischen Anforderungskontexten? - Abele, Stephan; Greiff, Samuel; Wüstenberg, Sascha; Funke, Joachim (Zeitschrift für Erziehungswissenschaft, 2012)
This article is about the importance and validity of dynamic problem solving (DPS) in predicting technical problem solving performances. In addition to DPS, fluid intelligence and technical knowledge were included in the study. Assessing DPS and fluid intelligence simultaneously also allowed for testing the empirical distinction between both constructs. Results are based on data of a sample of car mechatronics (n = 129) and electronics technicians (n = 88) and showed that DPS and fluid intelligence were empirically separable. In the first sample (electronics technicians) DPS explained technical problem solving performance best, although fluid intelligence showed incremental validity too. In the second sample (car mechatronics) fluid intelligence was weakly related to the criterion whereas DPS was not at all. When technical knowledge was added to the prediction, both DPS and fluid intelligence did not predict technical problem solving performance. However, in the sample of the electronics technicians fluid intelligence indirectly affected the criterion through technical knowledge. A discussion of the somewhat contradictory results, the different results patterns in the two samples and a theoretical explanation of the results are provided.